การวิเคราะห์การจัดแฟ้มข้อมูลในระบบพัสดุคงคลังของการไฟฟ้าฝ่ายผลิต แห่งประเทศไทย - ภัททิมา จตุรพิธพร (จุฬาลงกรณ์มหาวิทยาลัย, 1980)
This research work describes a procedure to design the optimal block size in the Indexed Sequential file in order to minimize the average search time and to maximize the usage of the disk storage. Some considerations are given as a guideline to determine the number of the indexed block level in the Indexed Sequential file. The existing EGAT inventory system is used as a bench mark for the comparison of the performance of the Indexed Sequentile file designed by the established procedure. The total average processing time is reduced to approximately 60 % of the present EGAT inventory system.